Wireless sensor network for real-time air pollution monitoring - Kadri, A.; Yaacoub, E.; Mushtaha, M.; Abu-Dayya, Adnan (2013 1st International Conference on Communications, Signal Processing and Their Applications, 2013)
This paper presents an ambient real-time air quality monitoring system. The system consists of several distributed monitoring stations that communicate wirelessly with a backend server using machine-to-machine communication. Each station is equipped with gaseous and meteorological sensors as well as data logging and wireless communication capabilities. The backend server collects real time data from the stations and converts it into information delivered to users through web portals and mobile applications. The system is implemented in pilot phase and four solar-powered stations are deployed over an area of 1 km 2 . Data over four months has been collected and performance analysis and assessment are performed. As the historical data bank becomes richer, more sophisticated operations can be performed.